A quantitative assessment of electronic commerce - Ludger Schuknecht; Rosa Pérez-Esteve (World Trade Organization (WTO), 1999)
This paper tries to assess quantitatively the role of electronic commerce in economic activity and in trade and tariff revenue collection. The share of value added that potentially lends itself to electronic trade represents around 30 percent of GDP, most importantly distribution, finance and business services. Electronic commerce is also likely to boost trade in many services sectors significantly. Despite the growing importance of electronic commerce for economic activity and trade, tariff revenue loss from electronic commerce is likely to be minimal. Trade in potentially digitizable media goods (such as music, software or books) which currently faces a tariff in some countries represents less than one percent of total world trade. The revenue collected on these products amounts to less than one percent of total tariff revenue in most countries. Even if some of this trade moved online, tariff revenue loss would be only a very small share of tariff revenue.
Keywords: F1; O3; 330; Electronic commerce; international trade; services trade; tariffs; tariff revenue; technological change